IDENTIFICATION OF THE MAIN DIRECTIONS OF ORGANIZATIONAL AND ECONOMIC SUPPORT OF EDUCATIONAL SERVICES MANAGEMENT IN UKRAINE - TKALENKO, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the main approaches to the interpretation of the concept of educational service, which consider it as: purposeful activity of participants in the educational process; the process of transmitting certain information for assimilation; a set of knowledge, skills, abilities and a certain amount of information, etc. It is established that the system of organization and management of education at the regional and state level as a whole is a set of interrelated elements: educational programs and state educational standards of different levels and orientations, networks of educational institutions that implement them regardless of organizational and legal forms, types and types, education management bodies and institutions and organizations subordinate to them. The problems inherent in the management of the modern education system of Ukraine are revealed: the lack of clear requirements for managers; uncertainty of the specific content of education management; negative consequences of the collapse of the previously existing management system (violation of the material supply system, lack of control and forecast of quantitative and qualitative characteristics of educational services). The specifics of educational services are determined, namely the combination of traditional characteristics of services and the inseparable connection of educational services with the source of their provision; changes in the quality of service when changing the level of staff; impossibility of preservation; intangible; active participation of the consumer in the process of providing educational services. The future main directions of organizational and economic support of management of educational services in Ukraine are determined: stimulation of effective demand for education through tax benefits; development of a control system for ensuring state educational standards, etc.